From Mother and Daughter : Poems, Dialogues, and Letters of Les Dames des Roches. - Roches, Madeleine (Other voice in early modern Europe., 2006)
Among the best-known and most prolific French women writers of the sixteenth century, Madeleine (152087) and Catherine (154287) des Roches were celebrated not only for their uncommonly strong mother-daughter bond but also for their bold assertion of poetic authority for women in the realm of belles lettres. The Dames des Roches excelled in a variety of genres, including poetry, Latin and Italian translations, correspondence, prose dialogues, pastoral drama, and tragicomedy; collected in From Mother and Daughter are selections from their celebrated oeuvre, suffused with an engaging and enduri.